Implementing an Exercise Physiology Clinic for Consumers Within a Community Mental Health Service: A Real-World Evaluation - Fibbins, Hamish; Edwards, Law; Morell, Rachel; Lederman, Oscar; Ward, Philip; Curtis, Jackie (Frontiers in Psychiatry, 2021)
Background: Physical activity significantly improves mental illness symptoms and physical health for people living with mental illness. Mental health services do not routinely provide their consumers with access to exercise professionals for physical activity engagement. Barriers exist to integrating physical activity as part of standard care including staff culture, finance, and resources. This study examines the feasibility of newly established exercise physiology clinic within a mental health service in Sydney, Australia. Methods: A single site, open trial was conducted in a community centre within a large mental health district. A meeting room was converted into a part-time exercise physiology clinic where individualised physical activity interventions were delivered by an accredited exercise physiologist. Outcome measures including BMI, cardiovascular fitness, and self-reported physical activity were collected. Results: A total of 84 mental health consumers (17% of eligible consumers within the mental health service) participated in the clinic on average for one exercise session weekly. Moderate-to-vigorous physical activity significantly increased and sedentary time significantly decreased (p<0.001). Conclusions: Exercise physiology clinics are feasible within mental health services and should be incorporated as part of standard care.